2012
DOI: 10.5604/15093492.1012404
|View full text |Cite
|
Sign up to set email alerts
|

Wyniki leczenia ubytków chrząstki stawu kolanowego z użyciem mezenchymalnych komórek macierzystych krwi.

Abstract: 1. The reconstruction of large cartilage lesions with peripheral blood stem cells is an effective treatment modality. 2. This method is a valuable alternative to autologous chondrocyte transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…All reference lists of the 17 included studies were investigated, and an additional human trial (Jancewicz et al, 2004) was identified and included in this review. Finally, data from the 18 studies [8 human studies (Jancewicz et al, 2004;Saw et al, 2011;Skowroński et al, 2012;Saw et al, 2013;Skowroński and Rutka, 2013;Turajane et al, 2013;Fu et al, 2014a;Saw et al, 2015) and 10 animal studies (Spaas et al, 2012;Broeckx et al, 2014a;Broeckx et al, 2014b;Fu et al, 2014a;Deng et al, 2015;Hopper et al, 2015b;Zhao et al, 2018;Daems et al, 2019;Broeckx et al, 2019a;Broeckx et al, 2019b) published by investigators from seven countries or regions] were analyzed.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…All reference lists of the 17 included studies were investigated, and an additional human trial (Jancewicz et al, 2004) was identified and included in this review. Finally, data from the 18 studies [8 human studies (Jancewicz et al, 2004;Saw et al, 2011;Skowroński et al, 2012;Saw et al, 2013;Skowroński and Rutka, 2013;Turajane et al, 2013;Fu et al, 2014a;Saw et al, 2015) and 10 animal studies (Spaas et al, 2012;Broeckx et al, 2014a;Broeckx et al, 2014b;Fu et al, 2014a;Deng et al, 2015;Hopper et al, 2015b;Zhao et al, 2018;Daems et al, 2019;Broeckx et al, 2019a;Broeckx et al, 2019b) published by investigators from seven countries or regions] were analyzed.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Among the 18 studies, 7 were case reports [6 in humans (Jancewicz et al, 2004;Saw et al, 2011;Skowroński et al, 2012;Turajane et al, 2013;Fu et al, 2014a;Saw et al, 2015) and 1 in horses (Spaas et al, 2012)], 1 was a human comparative study (Skowroński and Rutka, 2013), 1 was a human randomized controlled trial (RCT) (Saw et al, 2013), 1 was a preliminary study (in horses) (Broeckx et al, 2014a), 1 was a pilot study (in horses) (Broeckx et al, 2014b), 4 involved animal models [rabbits (Fu et al, 2014b), sheep (Hopper et al, 2015b), rats (Deng et al, 2015), and pigs (Zhao et al, 2018), 1 was a prospective placebocontrolled study (in dog) (Daems et al, 2019), and 2 were randomized, double-blinded, placebo-controlled proof-ofconcept study (in horses) (Broeckx et al, 2019a;Broeckx et al, 2019b) (Table 1). (Jancewicz et al, 2004) Human 9Case report N/A N/A Osteochondral defects Talus 0.5×0.7 cm with 0.5-1.0 cm depth ICRS IV (Skowroński et al, 2012 The age of the patients ranged from 7 to 59 years in the 8 human studies (Jancewicz et al, 2004;Saw et al, 2011;Skowroński et al, 2012;Saw et al, 2013;Skowroński and Rutka, 2013;Turajane et al, 2013;Fu et al, 2014a;Saw et al, 2015). Lesions were mainly located in the tibial plateaus (Saw et al, 2011;Saw et al, 2013), patella (Saw et al, 2011;Skowroński et al, 2012;Saw et al, 2013), femoral condyles…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Injection of peripheral blood MSCs allowed improvement in the KOOS, Lysholm score, visual analog scale, and KOOS pain scale in patients with ICRS grade 3 or 4 lesions for up to 6 years 198. Moreover, second-look arthroscopies of subchondral drilling of ICRS grade 3 and 4 lesions in patients combined with five weekly injections of peripheral blood MSCs in hyaluronic acid starting one week postoperatively revealed a well-integrated repair tissue of fibrocartilaginous and hyaline-like cartilaginous aspect without delamination or hypertrophy after 3 months compared with hyaluronic acid treatment alone 196,197.…”
Section: Applications For Articular Cartilage Defectsmentioning
confidence: 96%
“…Intra-articular stem cell injections for the clinical treatment of focal lesions so far have only been investigated in conjunction with marrow stimulation procedures, based on the use of bone marrow-derived MSCs195 and peripheral blood MSCs196198 (Table 1). …”
Section: Applications For Articular Cartilage Defectsmentioning
confidence: 99%